Potential of Lactic Acid Bacteria Isolated from Dangke and Indonesian Beef as Hypocholesterolaemic Agent - H. Burhan; S. A. Priyambada; E. Taufik; I. I. Arief (Faculty of Animal Science, Bogor Agricultural University, 2017)
Lactobacillus fermentum strains were successfully isolated from dangke which was a fresh cheese-like product originating from Enrekang, South Sulawesi Province, Indonesia. In addition, Lactobacillus plantarum and Lactobacillus acidophillus were isolated from beef. This study aimed to investigate the ability of those 8 LAB strains from dangke and beef in lowering cholesterol level by using in vitro study. Strain of Lactic acid bacteria used were L. fermentum strains (A323L, B111K, B323K, C113L, C212L), L. plantarum strains (IIA-1A5 and IIA-2C12), and L. acidophillus IIA-2B4. Variables observed were identification of Bile Salt Hydrolase (BSH) gene by Polymerase Chain Reaction (PCR), BSH activity and cholesterol assimilation. Phylogenetic tree indicated homology of L. plantarum IIA-IA5 was 98% to BSH gene of L. plantarum Lp529 with access code of FJ439771 and FJ439775 obtained from GenBank. The results demonstrated that eight strains of LAB isolated from dangke and beef that potentially showed cholesterol-lowering effects were L. fermentum B111K and L. plantarum IIA-1A5. L. fermentum B111K was able to assimilate cholesterol by 4.10% with assimilated cholesterol of 0.13 mg in 1010 cells. In addition, L. plantarum IIA-1A5 had BSH gene and BSH activity, as well as the ability to assimilate cholesterol by 8.10% with assimilated cholesterol of 0.06 mg in 1010 cells. It is concluded that L. fermentum B111K and L. plantarum IIA-1A5 were strains that showed cholesterol-lowering effects.